Enantioselective and Diastereoselective Conjugate Radical Additions to α-Arylidene Ketones and Lactones - Zhao, Changjia; Sibi, Mukund P. (Synlett, 2017)
A highly stereoselective conjugate radical addition to arylidene ketones and lactones has been developed. The conjugate radical additions using chiral salen Lewis acids proceeds with up to 99:1 dr and 87% ee in good to excellent chemical yields.
Keywords: enantioselective radical reaction; arylidene ketones and lactones; diastereoselectivity; conjugate addition; chiral salen Lewis acid